IMPLIKASI PARADIGMA ALIRAN-ALIRAN FILSAFAT TERHADAP MANAJEMEN SUMBER DAYA MANUSIA DI SEKOLAH - Hani Hadiati Pujawardani; Mohammad Hasan; Achmad Saefurridjal (Komitmen: Jurnal Ilmiah Manajemen, 2023)
Education has principles on which it stands in material, interaction, innovation and its ideals. So it's like medicine, engineering or agriculture, for example. Each cannot stand alone, but is an arena where a number of sciences are practiced which are closely related to each other and intertwine. Efforts in educational practice always make comparisons of educational philosophies or educational history of nations that influence a nation's outlook on life. Thus, the concept of education can change according to the development of society and the development of human culture. In other words, the concept of education cannot be separated from educational practices that must be in accordance with the demands of educational needs at that time, until now. Philosophy has a close relationship with education, both in the theoretical and practical sense. Every educational theory is always based on a certain philosophical system on which it is based. Likewise, all educational practices that are pursued in earnest are actually based on a philosophical thought which is the driving ideology. The paradigms of philosophical schools with the establishment of vision and mission and educational programs have a fairly close relationship. The paradigm of philosophical schools is the principle used by an institution to formulate and define a vision, for example, and an educational program.